Multicultural-Based Islamic Religious Education Assessment Strategy to Improve Students' Tolerance - Sukowati, Nur Laila; Yuanda, Noni; Fajrin, Nadhifa (Journal of English Language and Education, 2025)
Indonesia, as a multicultural country, faces challenges in managing diversity to prevent it from becoming a source of conflict. Multicultural education is recognized as a strategic approach to instill values of tolerance and mutual respect. Within this context, Islamic Religious Education (IRE) holds a crucial role in shaping the nation's moral foundation and preparing students to live harmoniously in a diverse society. This study aims to explore the integration of assessment frameworks in IRE to holistically develop students' competencies, particularly their awareness and understanding of multiculturalism. Employing a library research method and content analysis of relevant sources, the study reveals that integrating Assessment of Learning (AoL), Assessment for Learning (AfL), and Assessment as Learning (AaL) into IRE-based instruction enriched with multicultural values can effectively support the internalization of tolerance. Teachers act as role models, while assessment strategies such as authentic assessment, attitude evaluation, values-based discussions, case studies, and peer assessments significantly contribute to nurturing students' tolerant character. Consequently, multicultural education supported by appropriate assessment strategies in IRE plays a vital role in shaping a generation of Indonesian youth who are intelligent, strong in character, inclusive, tolerant, and capable of contributing positively to a diverse society. However, schools alone, as agents of social change, may not be sufficient to fully optimize learning and assessment processes that support the internalization of multicultural and religious moderation values.